Dyspnea in focus: Insights on assessment - Belo, Letícia Fernandes (2023)
Dyspnea is a limiting symptom in several populations, and one of the main symptoms reported by individuals with chronic obstructive pulmonary disease (COPD). The progression of dyspnea correlates with disease progression. In early stages of COPD, the complaint of dyspnea is more common during exertion, while in severe stages the subjects report a limitant sensation sometimes even at rest. In addition, dyspnea leads to impaired quality of life and hindered performance in activities of daily living. Concomitantly, a reduction in the level of physical activity in daily life increases the risk of death. In recent years there has been growing interest in the study of all facets of this symptom. However, there are still several gaps in the literature to be addressed, especially with regard to the physiological mechanisms that trigger dyspnea during exertion and its evaluation methods. Objectives: This thesis has the aim of contributing to the scientific evidence related to the dyspnea assessment specifically by: 1) comparing the clinical and physiological variables of individuals with and without COPD who stop exercising due to dyspnea versus others symptoms; and 2) making available a multidimensional tool for dyspnea assessment for Portuguese-speaking individuals with COPD. Methodology: Two original studies were developed: (1) The first study discriminated the proportion of individuals with and without COPD according to their reason to stop the exercise. Furthermore, the physiological responses at the peak of the exercise were verified and compared between groups, as well as their pulmonary function and clinical data; (2) In the second study, the translation, validation and reproducibility of the Portuguese version of the Multidimensional Dyspnea Profile (MDP) were proposed. Results: Study (1) demonstrated that, independently of COPD diagnosis, individuals who stop exercising due to dyspnea present changes such as hyperinflation and restriction of lung volumes, even with preserved exercise capacity, compared to individuals who stop for another reason. Study (2) showed that the Portuguese version of the MDP is a valid and reproducible tool for assessing this symptom in individuals with COPD. Conclusions: The two scientific articles contained in this thesis add novel information to the available literature on dyspnea in individuals with COPD. Rregardless of lung function, age and BMI, individuals who stop exercise due to dyspnea have greater lung restrictions than individuals who stop exercise for other reasons. Moreover, dyspnea can now be confidently assessed multidimensionally in Brazilian individuals with COPD.